ISOLATION AND STRUCTURAL IDENTIFICATION OF TRITERPENE COMPOUNDS FROM THE LEAVES OF RUBUS ANNAMENSIS CARDOT COLLECTED IN LAM DONG PROVINCE - Thi Diem Trinh Le; Le Hue Anh Nguyen; Thi Ngoc Bich Tran; Thi To Uyen Nguyen; Thanh Truc Huynh; Thi Diep Trinh (Tạp chí Khoa học Đại học Đà Lạt)
From the leaves of Rubus annamensis Cardot collected in Lam Dong Province, two triterpene compounds were isolated and identified as niga-ichigoside F1 (2α,3β,19α,23-tetrahydroxy-urs-12-en-28-oic acid-β-D-glucopyranosyl ester) and ursolic acid (3-beta-3-hydroxy-urs-12-ene-28-oic acid) by using chromatographic and spectroscopic methods (IR, 1H-NMR, 13C-NMR, DEPT, HSQC, HMBC, and ESI-MS). This is the first time these compounds have been isolated from Rubus annamensis.